2018
DOI: 10.1039/c7sc04521b
|View full text |Cite
|
Sign up to set email alerts
|

A modular synthetic route to size-defined immunogenicHaemophilus influenzaeb antigens is key to the identification of an octasaccharide lead vaccine candidate

Abstract: A Haemophilus influenzae b vaccine lead antigen was identified by the immunological evaluation of chemically precisely defined capsular polysaccharide repeating unit oligosaccharides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…1b). Immunogenicity studies of the synthesized conjugates 2–5 on Zika rabbit model revealed that tetrameric conjugate 2 is the sufficient epitope for the new synthetic glycoconjugate Hib vaccine [42].
Fig.
…”
Section: Main Textmentioning
confidence: 99%
“…1b). Immunogenicity studies of the synthesized conjugates 2–5 on Zika rabbit model revealed that tetrameric conjugate 2 is the sufficient epitope for the new synthetic glycoconjugate Hib vaccine [42].
Fig.
…”
Section: Main Textmentioning
confidence: 99%
“…Early work on polysaccharides produced a series of three‐dimensional structures derived from X‐ray diffraction of fibers. The conformation in solution, crucial to understand the biological functions of polysaccharides, remained elusive due to lack of proper analytical techniques. The high structural diversity results from the different monosaccharide units (e.g., glucose, galactose, mannose) which can be substituted with multiple functional groups (e.g., acetyl, amine, sulfate).…”
Section: Introductionmentioning
confidence: 99%
“…A similar length‐dependent immunological activity was observed for the Haemophilus influenzae b antigens . Chemically synthesized glycoconjugates containing oligoribosyl‐ribitol‐phosphate (PRP) with 4 to 10 repeating units show different immunogenicities, with the tetramer and octamer able to elicit the highest antibody levels.…”
Section: Glycans Conformationmentioning
confidence: 67%